Analisis Pengaruh Kepemimpinan dan Fasilitas Kerja Terhadap Kinerja Pegawai Puskesmas Jatimulya, Kabupaten Bekasi - Sri Waluya; Edison (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
Jatimulya Health Center is a community health center whose performance needs to be improved. Its current performance is still not optimal. The title of this research is Analysis of the Influence of Leadership and Work Facilities on the Performance of Jatimulya Health Center Employees, Bekasi Regency. This study aims to determine whether leadership and work facilities have an influence on employee performance at the Jatimulya Health Center. Research data comes from library research, field research, data from questionnaires. The theoretical basis used is leadership theory, work facility theory and performance theory. Methods of data analysis using validity test, reliability test, classic assumption test, multiple linear regression analysis, analysis of the coefficient of determination, t test and F test using the SPSS 23 application. Based on the results of the data analysis carried out (Y = 9.244 + 0.267 X1 + 0.453 X2), it is concluded that the leadership variable (X1) has a positive and significant influence on employee performance. The work facility variable (X2) also has a positive and significant influence on employee performance. The test results for the coefficient of determination (R2) of 0.503 means that the employee performance variable is influenced by the leadership and work facilities variable by 50.3% and the remaining 49.7% is influenced by other factors that are not examined. The results of the F test show Fcount 13.467 > Ftable 3.35, leadership and work facilities together have a significant influence on employee performance.